Wings of fire. Book three , The hidden kingdom : the graphic novel - Sutherland, Tui, 1978-; Swirsky, Rachel; Deutsch, Barry (Wings of fire, the graphic novel, 2019)
"The Dragonet Prophecy didn't call for a RainWing dragonet, but Glory knows she's far more powerful than she gets credit for. So it's devastating when she finally finds the rest of her tribe and discovers that RainWings do seem a little lazy. They nap every day, no one really wants to be queen, and worst of all, only a few have noticed that RainWings are disappearing--mysteriously vanishing from the safety of the rain forest without a trace. Glory is determined to find the missing dragons, even if it means dragging her peaceful tribe where they never wanted to be: right into the middle of the war."--Provided by publisher